Design of an IoT-Based Aquaculture Monitoring System Based on IoT in Fish Farming - Ari Subowo; Nanang Pradita (ENERGY: JURNAL ILMIAH ILMU-ILMU TEKNIK, 2025)
Maintaining optimal water quality is essential for achieving high productivity in aquaculture. However, conventional monitoring practices among small-scale fish farmers remain manual and inefficient. This study presents the design and evaluation of a low-cost Internet of Things (IoT)-based water quality monitoring system tailored for rural aquaculture applications. The prototype integrates an ESP8266 microcontroller with pH, Total Dissolved Solids (TDS), and temperature sensors to enable real-time data collection and automated control. Field testing was conducted in a 2 × 3 × 1 m fish pond for seven days with data sampling every 5 minutes. The system achieved an average transmission latency of 4.2 seconds and 99 % data-delivery reliability. Measurement accuracy compared to manual instruments showed deviations of ±0.08 pH, ±0.4 °C, and ±15 ppm TDS. With a total hardware cost of approximately Rp 950,000 (≈ USD 60), the proposed system demonstrates a practical, reliable, and affordable solution for continuous water-quality monitoring, supporting sustainable fish farming in rural areas.